(untitled) (Paris, 1970)
Drawing on American and Japanese songs, slogans, cartoons, propaganda films, secret reports, and a wealth of other documents of the time, Dower opens up a whole new way of looking at that bitter struggle of four and a half decades ago and its ramifications in our lives today. As Edwin O. Reischauer, former ambassador to Japan, has pointed out, this book offers "a lesson that the postwar generations need most...with eloquence, crushing detail, and power."
Keywords: World war, 1939-1945,Japan; History